Entwicklung eines Zellkulturmodells zur Untersuchung des Schadstoffeinflusses auf Seehunde (Phoca vitulina) ... : Development of a cell culture model to assess the impact of pollutants on harbour seals (Phoca vitulina) ... - Wargel, Antonia (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2011)
Within the Trilateral Monitoring and Assessment Program for the Wadden Sea harbour seals (Phoca vitulina) are considered as sensitive indicators for the status of the Wadden Sea ecosystem. Due to their position as top predators in the marine food web and their long live spans, harbour seals are particularly burdened with persistent pollutants like polychlorinated biphenyls (PCBs) and perfluorooctane sulfonate (PFOS). These pollutants accumulate in the food web and numerous studies are indicating that they can cause severe effects on the health of chronically exposed organisms. The present study contributes to current efforts undertaken to identify novel biomarkers for pollutant exposure of wild-ranging seals. For the early diagnosis of disorders caused by anthropogenic pollutants, pollutant-induced up- or downregulation of protein expression in hepatocytes presents a potential marker. The aim of the present work was the elaboration of a cell culture model that enables the identification of proteins suiting ... : Der Seehund wird in Monitoring-Programmen zum Zustand des Ökosystems Wattenmeer (z.B. TMAP) als ein Indikatororganismus genutzt. Aufgrund der Position im Nahrungsnetz (Top-Prädatoren) und der langen Lebensspanne sind Seehunde besonders stark mit Schadstoffen belastet, u.a. mit Polychlorierten Biphenylen (PCB) und Perfluoroctansulfonat (PFOS). Zahlreiche Studien deuten darauf hin, dass die Schadstoffbelastung die Gesundheit der Seehunde beeinträchtigt. Das Ziel unserer Arbeitsgruppe ist die Identifizierung neuer Biomarker, die im Lebendmonitoring von Seehunden eingesetzt werden können. Ziel der vorliegenden Arbeit war die Ausarbeitung und Etablierung eines Zellkulturmodells, welches in weiterführenden Arbeiten die Identifizierung der Biomarker ermöglicht. Als Biomarker sollen Proteinmuster verwendet werden, die eine Früherkennung von schadstoffbedingten Veränderungen in der Seehundpopulation ermöglichen. Da Hepatozyten an der Metabolisierung von Xenobiotika beteiligt sind, werden sie für das Zellkulturmodell ...